2004
DOI: 10.1111/j.1445-1433.2004.03184.x
|View full text |Cite
|
Sign up to set email alerts
|

Mirizzi syndrome: noteworthy aspects of a retrospective study in one centre

Abstract: The preoperative diagnosis of Mirizzi syndrome is a challenge. Only constant vigilance during intraoperative dissection of the Calot's triangle will reduce the incidence of bile duct injury in Mirizzi syndrome that can occur in both open and laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 14 publications
5
42
2
1
Order By: Relevance
“…The characteristic feature of Mirizzi syndrome in USG is stone impaction in gallbladder neck with dilatation of proximal biliary system. Although USG is the initial imaging modality, it has limited sensitivity of 8% to 48% in the diagnosis of Mirizzi syndrome [2,9]. Computed topography (CT) scan can identify dilated intrahepatic and extrahepatic ducts with stones in biliary tree but has poor sensitivity of about 40% to 50% [2,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic feature of Mirizzi syndrome in USG is stone impaction in gallbladder neck with dilatation of proximal biliary system. Although USG is the initial imaging modality, it has limited sensitivity of 8% to 48% in the diagnosis of Mirizzi syndrome [2,9]. Computed topography (CT) scan can identify dilated intrahepatic and extrahepatic ducts with stones in biliary tree but has poor sensitivity of about 40% to 50% [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…Although ERCP has a variable sensitivity of 50% to 100% in the diagnosis of Mirizzi syndrome, it is the most accurate imaging technique to identify the cholecysto-choledochal fistula and offers therapeutic drainage of biliary tract [2,3,9]. Increasingly, MRCP has been used for the diagnosis of Mirizzi syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A colangioressonância e a TC podem ajudar a diferenciar a síndrome de Mirizzi de malignidades do sistema biliar extrahepático 19 . A colangiografia endoscópica retrógrada mostrará as anormalidades dos ductos biliares e a fístula, entretanto, pode apresentar algumas complicações 22 . Nestes pacientes, o diagnóstico foi intra-operatório em 100% dos casos.…”
Section: Discussionunclassified
“…However, cases not associated with CBD obstruction symptoms may be diagnosed as GB stone requiring only laparoscopic cholecystectomy. In a series reported by Tan et al [5] , bile duct injuries were observed in 4 (16.7%) of 24 operatively treated patients, and all the 4 injuries occurred in patients without a preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases have so far been reported, and various operations have been suggested depending on the types of MS. Laparoscopic cholecystectomy has become the standard operation for gallstones, and many authors have adopted this operation for typeⅠMS. However, high rates of conversion and bile duct injury indicate that this is not a safe treatment modality for MS, especially when combined with a cystic duct anomaly [2][3][4][5] . In this report, we present a case of type ⅠMirizzi syndrome, complicated by a rare anomalous cystic duct, which was operated with an open procedure.…”
Section: Introductionmentioning
confidence: 99%